Milk Processing: Review - Er. Ashok Kumar Das, Prof. Saroj Kumar Mohanty, Miss Monalisa Das (International Journal of Modern Agriculture, 2020)
The goal was to establish approaches to the treatment and conservation of local milk in the LIPTAKO-GOURMA region of Niger. The conference comprises 600 milk industry members, 59% producers, 28.7% customers and 12.3% traders. Production data of 59%. Two primary milk processing forms were also reported: cooling and oxidation, which included 42.9% natural/spontaneous germination and 57.10% processor-based fermentation. Four methods were also set out for milk preservation, namely crude milk refrigeration, pasteurized or preserved milk, raw milk or hydrogenated milk fermentation, pasteurization of crude milk itself for sale or storage including insertion of a cocoon pepper cap into the fermented milk. Milking is still traditional and the use of old stuff is usually limited to the absolute lowest possible level. In view of these findings, the education of farmers on health and good practice to improve conventional methods at all levels of the local milk sector should be paid attention